Reconstruction of Extended Scalp Defects with Free Flaps - Galip Gencay Üstün; Güven Ozan Kaplan; Murat Kara; Gökhan Sert; Hakan Uzun (Turkish Journal of Plastic Surgery)
Introduction: The reconstruction of extensive scalp defects often requires free tissue transfer, offering single-stage and reliable reconstruction. The aim of this study is to evaluate the outcomes of free tissue transfer in scalp reconstruction. Patients and Methods: Thirteen patients were included in the study. Patient age, gender, smoking status, comorbidities, defect etiology, the specific type of flap used, the chosen recipient artery and vein, the need for revision, and flap success were reviewed. Results: The majority of the patients were male (76.9%). Defect reconstruction was performed using the latissimus dorsi musculocutaneous flap in 10 (71.4%) cases, which was followed by anterolateral thigh (ALT) and vertical rectus abdominis flaps. Two patients needed expansion of latissimus dorsi flaps. Superficial temporal vessels were used as recipient vessels in most patients. Three patients required anastomosis revision, all of which resulted in flap success. Conclusion: The high success rate observed in this study may be attributed to close monitoring of patients in the postoperative period and quick, early decision-making for revisions when necessary. The latissimus dorsi flap is the best option when large area coverage is needed, while the ALT flap is preferred when minimizing donor site morbidity is a priority. The vertical rectus abdominis myocutaneous flap offers the advantage of a long pedicle for anastomosis, though it comes with higher donor site morbidity. The superficial temporal artery and vein are reliable recipient vessels for scalp reconstruction.